Image of India in the Indian novel in English, 1960-1985 - Pandey, Sudhakar; Raj Rao, R. (Ramachandrapurapu), 1955-; India. University Grants Commission; UGC Seminar on the Image of India in the Indian Novel in English (1986 : University of Poona) (Hyderabad : Orient Longman, 1993)
Papers presented at the UGC Seminar on the Image of India in the Indian Novel in English, 1960-1985, organized by University Grants Commission at the University of Poona in March 1986.
Includes bibliographical references and index.
Keywords: Indic fiction (English) -- 20th century -- History and criticism; India -- In literature